Plerixafor in combination with chemotherapy and/or hematopoietic cell transplantation to treat acute leukemia: A systematic review and metanalysis of preclinical and clinical studies. (October 2020) - Maganti, Harinad; Visram, Alissa; Shorr, Risa; Fulcher, Jill; Sabloff, Mitchell; Allan, David S.
Highlights: Plerixafor, a CXCR4 antagonist, can mobilize and sensitize leukemia cells to cytotoxic therapy. In our systematic review, preclinical studies confirm that leukemia cells can be mobilized. Plerixafor can reduce tumor burden and improve survival of animals. Clinical studies demonstrate relative safety and feasibility of using plerixafor. Patients with high levels of CXCR4 expression on leukemia cells are worthy of future study. Abstract: Leukemia-initiating cells localize to bone marrow niches via cell surface CXCR4 binding to stromal-derived factor 1 (SDF-1). Plerixafor, a CXCR4 antagonist, can mobilize and sensitize leukemia cells to cytotoxic therapy, and/or enhance the engraftment of healthy donor stem cells in the context of hematopoietic cell transplantation (HCT). A systematic review of preclinical and clinical studies was performed (updated May 1, 2020) to inform the design of definitive clinical trials and identified 19 studies. Pooled data from 10 preclinical in-vivo studies of AML and ALL in mouse models of leukemia revealed significant mobilization of leukemia cells into the peripheral circulation, decreased total blast burden and increased survival with plerixafor in addition to cytotoxic treatment compared to control animals. Two of 9 clinical studies compared outcomes to a control group. Plerixafor appears well tolerated and safe and can mobilize leukemia cells into the peripheral circulation. In patients with AML undergoing HCT, plerixafor given with the conditioning regimen appears safe and well tolerated. Engraftment, relapse and survival were not different from controls after limited follow-up. Studies in high risk patients with AML with longer follow-up are needed to understand the influence on relapse following treatment and on donor cell engraftment following HCT.